Chapter Citizen science based marine environmental monitoring. The MOANA60 Experience - Viola, Alberto (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Sea water quality monitoring is extremely demanding and expensive. This results in the sea being largely under-sampled. To solve this OGS developed innovative technologies to be used within a citizen science approach. The simultaneous installation of remote sensing devices on boats of opportunity allows to build a monitoring infrastructure able to acquire, process, validate and display in real-time georeferenced data on a web portal. This work reports on a survey done in collaboration with the Moana 60 Lab initiative in the South Thyrrenian Sea.